ดีออกซิจิเนชันของไบโอออยล์ที่ได้จากไพโรไลซิสของกระถินยักษ์ Leucaena leucocepphala โดยใช้แพลทินัมรองรับบนอะลูมินา - จิราพร พยอมหอม (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This article studied the quality improvement of bio-oil obtained from pyrolysis of Leucaena leucocephala via deoxygenation catalyzed by platinum supported on alumina (Pt/Al₂O₃). For this research studied the condition of deoxygenation such as catalyst loading, temperature, reaction time, initial pressure of nitrogen and hydrogen content. The deoxygenation found that the reaction temperature of 420℃ under N₂ atmosphere for 1 hour and using 10% (w/w) of Pt/Al₂O₃ was the condition to eliminate the oxygenated compounds in the bio-oil ca. 94% via steam reforming, water-gas shift reaction and dehydration. To consider the chemical compounds of bio-oil derived from pyrolysis Leucaena luecocephala, rice straw, algae and sawdust, the results indicated that bio-oil derived from pyrolysis of algae gave the highest of oxygen removal as ca. 94%. The chemical compounds in bio-oils obtained from pyrolysis of these biomass were analyzed by using a gas chromatography-mass spectrophotometer (GC-MS) before and after catalytic deoxygenation. The results showed that Leucaena leucocephala and sawdust, which are hard woods were composed with higher lignin content. It gave the product of bio-oil with more complexity of oxygenated compounds such as the phenol and its derivatives in the bio-oil, resulting in the higher difficulty to remove oxygenated compounds than algae and rice straw.